TEACHING ENGLISH ON COLORS TO MAKE SENTENCE AT SMK COKROAMINOTO KOTAMOBAGU - Muhamat A. Samidu; Nihta V.F. Liando; Veronika L. F. Damopolii (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
Tenses are the bases in learning English. Whether we agree or not learning tenses is recommended for students to master English. Students at SMK Cokroaminoto Kotamobagu still find tenses difficult. That is the main reason of the researcher to conduct this research. This research aims at finding out whether color symbols is effective or not for students to learn tenses, in paricular Simple Past Tense. This is a pre-experimental research with pre and post - tests design. There are 13 tenth-grade students involved in this research. Pre-test and post-test were used in obtaining the data. The data in this research were analyzed statistically using mean score formula. The result of this study shows that the scores of Post-Test’s is higher than those of Pre-Test. The researcher could say that there is significant difference in the students’ understanding about Tenses by using Color Symbols. These results led to a conclusion that Color Symbols are considered effective to improve students’ ability to understand Simple Past Tense.